Miniatur Rancang Bangun Penerangan Lampu Jalan Otomatis Pada Malam Hari Menggunakan Sensor Ultrasonik Berbasis Arduiono Mega - Syafira Lubis, Maharani (Teknologi Rekayasa Jaringan Telekomunikasi, 2021)
Through this problem, it can be done by making a design that uses a technology system. The technology system designed is to make automatic street lighting, which is controlled by the Arduino Mega Microcontroller and Ultrasonic Sensor. Ultrasonic Relays and Sensors use the current in the Arduino, Arduino has a work of 5v. For use, this relay functions as a controller while the current is separate. Battery usage is also used in this design, namely in order to turn on the LED which is being used as an example of an automatic lamp in the automatic lamp design. For the way the automatic light works is to read the Ultrasonic sensor of a vehicle so that it can turn on the light and relay. used, to turn on the current. Then if there is a form of movement, the relay will turn on and automatically the lights are ON. So if a vehicle moves towards the lighting, the light will automatically turn on and illuminate the road, so that after the vehicle passes, the light will automatically turn off in order to save electricity in the road area.